2006
DOI: 10.4025/actascianimsci.v28i2.654
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da suplementação de selenometionina e vitamina C sobre as características quantitativas e qualitativas do sêmen de coelho

Abstract: Foram avaliadas as características quantitativas e qualitativas do sêmen de coelhos alimentados com rações contendo diferentes níveis de selenometionina e vitamina C (VC). Utilizaram-se 125 coelhos machos, alojados individualmente e distribuídos em um delineamento experimental inteiramente casualizado, com vinte cinco tratamentos e cinco repetições. As colheitas de sêmen foram realizadas uma vez por semana, durante oito semanas. Os parâmetros avaliados foram: volume, cor, pH, motilidade espermática progressiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…By [58], normal semen is white, homogeneous and opalescent. According to [65], the colour of rabbit semen is white with the intensity dependent on the concentration of the sperm. He further reported that milky-white semen is the best and predominant in the rabbit and represents normal semen with good quality, while [64] reported that rabbit ejaculate is mostly milky-white but the best quality is found in creamy-white semen.…”
Section: Semen Colourmentioning
confidence: 99%
“…By [58], normal semen is white, homogeneous and opalescent. According to [65], the colour of rabbit semen is white with the intensity dependent on the concentration of the sperm. He further reported that milky-white semen is the best and predominant in the rabbit and represents normal semen with good quality, while [64] reported that rabbit ejaculate is mostly milky-white but the best quality is found in creamy-white semen.…”
Section: Semen Colourmentioning
confidence: 99%
“…A metodologia para avaliação do pH das amostras foi realizada seguindo o descrito por Alvarez, et al (2006) e OMS, (2010). As amostras foram medidas em um tempo uniforme, sempre menor que 30 minutos após a colheita, utilizando-se papel de pH na faixa de 0,0 a 14,0.…”
Section: Phunclassified